Energy Transition in and by the Local Media - Horsbøl Anders (Nordicom Review, 2013)
Climate change mitigation and the transition to environmentally sustainable forms of life have become central public issues, and a number of studies have investigated the role of the media in constructing and distributing representations of climate change and sustainability. Most of these studies have addressed the media at a national or international level. This article investigates the mediating of a local, municipal initiative, i.e. the so-called ‘Energy Town Frederikshavn’ project in northern Denmark, which has set the ambitious goal of complete transition to renewable energy consumption and CO2 neutrality within a few years. Using frame analysis, informed by discourse studies, the article analyzes how the project emerged and was established as a public phenomenon in the media coverage, including how it was made intelligible and which social actors were represented as having a say on the matter. The findings show several differences to national or international representations of climate change and sustainability, such as a prevalent profiling frame and an indication of a reversal of the so-called Giddens’ paradox.